2006
DOI: 10.1002/bdra.20217
|View full text |Cite
|
Sign up to set email alerts
|

Neural tube development requires the cooperation of p53‐ and Gadd45a‐associated pathways

Abstract: BACKGROUND:Numerous genetically engineered mouse models for neural tube defects (NTDs) exist, and some of the implicated proteins are functionally related. For example, the growth arrest and DNA damageinducible protein Gadd45a and tumor suppressor p53 are functionally similar, and both are involved in neural tube development (Gadd45a-and Trp53-null embryos show low levels of exencephaly). To assess their roles in neural tube development, we generated double-null mice from Gadd45a-and Trp53-null mice, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…Of the 98 mice at postnatal day one (P1), 13 were homozygous Trp53 null (À/À), of which all were male (Table 1, p ¼ 0.0009, FET). The 100% lethality in females is higher than has been reported for Trp53 null mice in the other inbred or outbred strains (Armstrong et al, 1995;Sah et al, 1995;Embree-Ku and Boekelheide, 2002;Patterson et al, 2006), suggesting that the effects of the mutation are greater on the B6 background.…”
Section: A Sex Chromosome Effect Causes Sex Difference In Lethality Ocontrasting
confidence: 60%
See 2 more Smart Citations
“…Of the 98 mice at postnatal day one (P1), 13 were homozygous Trp53 null (À/À), of which all were male (Table 1, p ¼ 0.0009, FET). The 100% lethality in females is higher than has been reported for Trp53 null mice in the other inbred or outbred strains (Armstrong et al, 1995;Sah et al, 1995;Embree-Ku and Boekelheide, 2002;Patterson et al, 2006), suggesting that the effects of the mutation are greater on the B6 background.…”
Section: A Sex Chromosome Effect Causes Sex Difference In Lethality Ocontrasting
confidence: 60%
“…DNA repair-deficient mice lacking XRCC4 or DNA ligase IV show embryonic lethality and massive neuronal apoptosis that is rescued by Trp53 mutation Gao et al, 2000). The NTD phenotype of Trp53 mutant mice is synergistically exacerbated by mutations in DNA damage response genes Gadd45a, XPC (Patterson et al, 2006) or Msh2 (Cranston et al, 1997;Cranston and Fishel, 1999). Together with Trp53, these functions are involved in apoptosis, genomic instability, cell cycle control, and/ or DNA repair and their absence leads to an accumulation of mutations and genome rearrangements.…”
Section: Trp53mentioning
confidence: 96%
See 1 more Smart Citation
“…[6] On the other hand, around 8-16% of p53-deficient female mice exhibited exencephaly,[15] and the levels of exencephaly increased in double knockouts for p53 and Gadd45a (growth arrest and DNA-damage-inducible protein alpha), which is a one of the downstream effectors induced by p53 to achieve G2-M arrest. [7] Pregnant p53 deficient mice are at higher risk of reduced blastocyst implantation;[16] however, development of neural tube or its defects, condition which is considered in the present study, arises only after the blastocyst implantation of an embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse model studies suggested suppression of p53 mediated apoptotic activity rescues NTDs,[46] but also, p53 deficient mice exhibit exencephaly. [7]…”
Section: Introductionmentioning
confidence: 99%